Analisis Peran Lembaga Keuangan Terhadap Pendapatan Usaha Mikro Kecil dan Menengah di Madura - Farisa Restu Fauziyah; Titov Chuk’s Mayvani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Micro, small, and medium enterprises play an important role in the economic development of a country, but the growth of MSMEs still often faces various challenges and has not been as expected. The low capital owned and the difficulty of MSMEs in accessing sources of financing are still problems that hinder the growth of MSME businesses. The role of financial institutions in the income of micro, small and medium enterprises in the Madura region is the focus of this study. The quantitative technique used in this study is linear regression analysis using dummy variables. This study found that the income of micro, small, and medium enterprises in Madura is significantly affected by the test factors of loan size, loan fee, and loan tenure. Of the three variables, the loan cost variable has the greatest influence on MSME income. The dummy variable of loan size shows an increase in income for MSME actors of 665,846.73 rupiah. The dummy variable of loan costs shows an increase in income for MSME actors of 3,708,001,234 rupiah. And the variable loan duration is 50,789.79 which shows that the loan duration has a positive effect on MSME income of 50,789.79 rupiah.